An Ultra‐sensitive Electrochemiluminescent Detection of Carcinoembryonic Antigen Using a Hollowed‐out Electrode. Issue 6 (11th March 2021) - Liu, Gen; Gao, Hui; Chen, Jiajia; Shao, Congying; Chen, Feifei
Abstract: Ultrasensitive detection of cancer biomarkers has attracted considerable attention recently in academic research and clinic diagnostics. Here, we use a hollowed‐out carbon nanotube sponge (CNTSP) electrode to fabricate an immunosensor to realize the sensitive detection of carcinoembryonic antigen (CEA). Nitrogen‐doped carbon quantum dots (N‐CDs) are combined with antibody that can specially recognize CEA and used as the electrochemiluminescent (ECL) probes in this work. The hollowed‐out and permeable CNTSP facilitates chemical species exchange on the surface of electrode, offering an enhanced ECL signal. The resulting ECL immunosensor enables the determination of CEA concentration to be in a wide linear range from 0.005 to 50 pg mL −1 with a detection limit of 1.4 fg mL −1 . Furthermore, with good stability, acceptable precision and reproducibility, the proposed ECL assay strategy offers a wide application potential in clinical analysis. Abstract :